(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to implement home visits based on the cooperative learning model as an innovative strategy to enhance the optimization of mathematics learning. The study involves students from SMP N 2 Karangsambung as research subjects. Data collection techniques include tests, interviews, and documentation. This research adopts the action research approach, involving cycles of planning, action, observation, and reflection. The results of the study indicate that the implementation of home visits with the cooperative learning model positively contributes to the optimization of mathematics learning. Concrete steps involve collaboration between teachers, students, and families to create a supportive learning environment. Classically, there has been an increase in the percentage of student learning mastery, with figures rising from 38.46% at the initial stage of the study (pre-cycle) to 50% in Cycle I, and further escalating to 76.92% in Cycle II. Additionally, there has been an enhancement in the overall student grade average, starting from 58.65 at the initial stage of the study to 69.80 in the first cycle, and then increasing to 79.03 in the second cycle. Both parameters, the percentage of learning mastery and the average student grade, in the second cycle have met the standards set as indicators criteria established